Some basic properties of cement board produced by using oil palm Empty Fruit Bunch (EFB) fibre - Abas, Nor Haslinda; Jaafar, Azman; Mat Seman, Ahmad Shakri (Penerbit Uthm, 2018)
The utilization of any kind of fibres in cement and concrete has been developed for several decades before. Many researches had been carried out on the incorporation of various kinds of fibres such as steel, polymer, glass, asbestos, carbon and wood fibres in cement matrix and most of the study revealed that the presence of fibres in cement matrix improves flexural strength, crack control, fracture toughness, resistance to fatigue, impact, and thermal shock, and resistance to moisture, fire, fungi and insect [1].